Erectile dysfunction after robotic radical prostatectomy: Real-life impact of vacuum erection device clinic. (September 2021) - Jones, Patrick; Sandoval Barba, Hector; Johnson, Mark I; Soomro, Naeem; Robson, Wendy; Ferguson, Jill; Aning, Jonathan J
Introduction: Post-radical prostatectomy erectile dysfunction (post-RPED) is a common and potentially devastating complication. The role of PDE5-inhibitors (PDE5-Is) in post-RPED is controversial and invasive pharmacological treatments are associated with poor long-term compliance. Vacuum erection devices (VEDs) are a non-pharmacological alternative. Little data regarding VED efficacy and associated patient satisfaction in post-RPED exists. This study aimed to investigate the outcomes of VED therapy in a post-robot assisted radical prostatectomy (post-RARP) population. Methods: All men who underwent RARP at a single centre between February 2015 and October 2017 attended a nurse-led holistic-needs-assessment (HNA) appointment at 10 weeks post-RARP. All men identifying ED as a concern at HNA were offered dedicated nurse-led post-RPED clinic and VED clinic appointments. A cross-sectional survey of patient reported outcomes in these men was performed. Results: In total 137/539 (25%) men reported ED as a concern at HNA. All 137 men attended the VED clinic, 124/137 (90%) responded to the survey. Commonest reason for choosing VED therapy was for combined psychological, penetration and lengthening purposes (48%). Median time from RARP to VED clinic and from VED clinic to survey was 122 days (range 56–595) and 462 days (range 66–932) respectively. At survey 88/124(70.9%) reported continued use of VED, 69/88 (78%) of this group perceived VED treatment to be successful. Of those who had stopped using VED, 7/36 (19%) felt it had been successful. Key reasons for discontinuation were either because men felt it ineffective (13/36 (37%)) or disliked the device (10/36 (29%)). Conclusion: VED therapy is an effective treatment for men with post-RARP ED that is well tolerated with good short- to medium-term compliance. Up to two-thirds of men may find overall satisfaction with their post-RPED after VED therapy. Level of Evidence: 3